Astronomical withdrawals: a green criminological examination of extreme energy mining on extraterrestrial objects - Lampkin, Jack 19XX- (Crime, law and social change, 2024)
Mining for natural resources on-Earth is commonplace and dates back over a hundred years at an industrial scale. Technological advances in outer space exploration are enabling the mining of extraterrestrial resources to transition from mere science fiction, to a serious possibility. In recent decades, several new start-up companies have arisen with the sole intention of exploiting resources that exist in outer space, such as on Earth’s moon, asteroids, meteorites, planets, and various planetary satellites, such as the moons of Mars - Phobos and Diemos. However, despite the increased investment and interest in space mining, criminologists have remained virtually silent on outer space issues. In this paper we adopt a green criminological approach to explain the emergence of outer space mining, and argue that now is the time to be researching and debating the phenomenon of extraterrestrial mining in order to prevent future social and environmental harm (following the precautionary principle of environmental law). To do this, the paper does three things. Firstly, it examines strategies for conducting space mining (such as its feasibility, probable locations, and innovative mining techniques). Secondly, it analyses the terrestrial and extraterrestrial impacts of space mining, unveiling several avenues for the creation of social and environmental harm. Finally, it uses a green criminological approach to justify the rationale for engaging legal scholars and criminologists with problematic space mining issues. The paper concludes that now is the time to discuss these issues, prior to the industrialisation and exploitation of unique celestial bodies.